2001
DOI: 10.1002/1097-0142(20011115)92:10<2508::aid-cncr1601>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose mitoxantrone and cyclophosphamide without stem cell support in patients with high‐risk and advanced breast carcinoma

Abstract: BACKGROUND Currently employed high‐dose regimens for patients with breast carcinoma consist mainly of single‐cycle combinations of alkylating agents. In a previous Phase I trial, the authors developed a tandem high‐dose combination of two cycles of mitoxantrone and cyclophosphamide for the treatment of patients with metastatic breast carcinoma (MBC) and high‐risk breast carcinoma (HRBC). Treatment was delivered with granulocyte‐colony stimulating factor (G‐CSF) but without stem cell support to avoid potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Tolerability of MX in dogs is good with myelosuppression being the dose‐limiting toxicity (Ogilvie et al ., 1991b, 1994). In humans, the drug has activity against tumours of epithelial origin, including tumours of the breast, prostate, pancreas, salivary gland and ovary (Devita et al ., 2001; Perez‐Garcia et al ., 2001; Tournigand et al ., 2001; Levine et al ., 2002). A combined phase I/II veterinary trial indicated a 20% response rate in dogs with carcinomas (Ogilvie et al ., 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…Tolerability of MX in dogs is good with myelosuppression being the dose‐limiting toxicity (Ogilvie et al ., 1991b, 1994). In humans, the drug has activity against tumours of epithelial origin, including tumours of the breast, prostate, pancreas, salivary gland and ovary (Devita et al ., 2001; Perez‐Garcia et al ., 2001; Tournigand et al ., 2001; Levine et al ., 2002). A combined phase I/II veterinary trial indicated a 20% response rate in dogs with carcinomas (Ogilvie et al ., 1991a).…”
Section: Introductionmentioning
confidence: 99%